The Influence of Environmental, Social, and Governance (ESG) Implementation on Corporate Cost of Capital With Financial Performance as A Moderating Variable (A Case Study on Companies in ASEAN) - Ivan Zuhdii Ardi Pradana; Inung Wijayanti (Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to analyze the impact of Environmental, Social, and Governance (ESG) performance on the cost of capital (WACC), as well as the influence of the company's financial performance (ROA) as a moderating variable, for companies listed on stock exchanges in ASEAN countries from 2018 to 2022. This study uses secondary data obtained from The London Stock Exchange Group (LSEG). The research sample is obtained through purposive sampling with predefined criteria, resulting in a sample of 1,161 observational data points. The data analysis techniques used include descriptive statistics, classical assumption tests, and multiple regression analysis using Eviews 12. The results of the study show that social performance has a significant positive impact on the cost of capital; environmental performance, when moderated by the company's financial performance, has a significant positive impact on the cost of capital; and social performance, when moderated by the company's financial performance, has a significant negative impact on the cost of capital. Meanwhile, the environmental and governance performance variables do not affect the cost of capital.